Aplikasi Pencarian Rute Optimal Antar Objek Wisata di Kabupaten Cilacap Berbasis Algoritma Floyd-Warshall - Salsadina, Nida Alifa; Rosyida, Isnaini (Universitas PGRI Semarang, 2025)
This research aims to build a tourism network by identifying optimal routes between tourist destinations based on node name data and distance between nodes. The method used is the implementation of the Floyd Warshall Algorithm, which is tested through two approaches. The first approach is done by running calculations using a special pyhton-based source code while the second approach is done through the design and use of route finding applications specifically designed in this research. The application in this study was designed using the waterfall method which consists of several sequential stages, namely requirements analysis, system design, implementation, system testing and system maintenance. The results show that both approaches produce identical routes and total distance traveled. The consistency of these results confirms the effectiveness of the Floyd Warshall Algorithm in determining the shortest route, as well as showing the potential of this application as an efficient travel planning tool.